Value addition in dairy farming: a methodological framework and case study analysis on milk processing and sales - Chie Onishi; Masashi Morie; Kenta Baba (Agricultural and Food Economics)
Abstract By processing and sales their products, farmers can enhance profits. However, marketing, especially pricing, is challenging. Profits arise from added value, and increasing this value in milk and dairy product sales can improve  profitability. Previous studies could only determine added value at the sales stage. This paper introduces the Onishi method, which calculates and evaluates added value at each processing and sales stage using a numerical value called PREMIUM. Analyzing Abe Farm in Japan with the Onishi method revealed that high added value in processing and strategic value addition in sales were key to profits. This also contributed to branding. Comparing Abe Farm with average dairy processing and sales cases in Spain showed that, despite positive profit margins, the PREMIUM for processed dairy products in the Spanish case was negative, indicating potential financial difficulties. We conclude that (1) the Onishi method quantifies added value at each stage, (2) successful cases show positive PREMIUM values at all stages, (3) the method can analyze and compare data regardless of country or currency, and (4) negative PREMIUM values can indicate financial difficulties despite positive profit margins.